1983
DOI: 10.1128/jb.155.3.1088-1093.1983
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct classes of polyuronide from the cell walls of a dimorphic fungus, Mucor rouxii

Abstract: Polyuronides were extracted from purified yeast and mycelial walls of Mucor rouxii by sequential treatments with lithium chloride and potassium hydroxide and were fractionated by ion-exchange chromatography on DEAE-Sephadex. Two polymers (I and II) of different acidity were found in both wall types. Polymer I contained D-glucuronic acid, L-fucose, D-mannose, and much smaller amounts of D-galactose. Yeast and mycelial polymer I had similar uronic acid contents but differed in their neutral sugar compositions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Table 1 displays the comparative composition of cell walls from Mucor yeasts, hyphae, sporangiophores, and sporangiospores. The main structural components of both yeast and hyphal walls are chitin and chitosan fibrils embedded within a matrix of the polyuronides mucoran and mucoric acid, glycoproteins, and glycopeptides (26,27,57,60). The contribution of the fibrillar components to the total mass of the cell wall is not much different in yeasts and hyphae.…”
Section: Composition and Construction Of The Cell Wall In Mucor Yeastmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 displays the comparative composition of cell walls from Mucor yeasts, hyphae, sporangiophores, and sporangiospores. The main structural components of both yeast and hyphal walls are chitin and chitosan fibrils embedded within a matrix of the polyuronides mucoran and mucoric acid, glycoproteins, and glycopeptides (26,27,57,60). The contribution of the fibrillar components to the total mass of the cell wall is not much different in yeasts and hyphae.…”
Section: Composition and Construction Of The Cell Wall In Mucor Yeastmentioning
confidence: 99%
“…Whereas Bartnicki-Garcia and Ruiz-Herrera have looked to the chitin-chitosan microfibrillar skeleton of the Mucor cell wall for the key to explaining dimorphism, Dow, Villa, and colleagues have focused on the polyuronide matrix components of the wall in search of correlates with morphogenesis (57,60,61). It is an entirely reasonable proposition that the properties of the mortar may be as important as those of the brick in defining the potential architecture of an edifice.…”
Section: Composition and Construction Of The Cell Wall In Mucor Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…It was designed as mucoran. The other polymer contained large amounts of D-glucuronic acid and was designed as mucoric or fungal β-(1,4) glucuronan acid [44]. Previous studies have also revealed the presence of β-(1,4)-D-polyglucuronic acid in the cell walls of several green algae [45,46].…”
Section: Polyglucuronic Acid From Bacteria Fungi and Green Algaementioning
confidence: 99%
“…It was designed as mucoran. The other polymer contained large amounts of d-glucuronic acid and was designed as mucoric or fungal β-(1,4) glucuronan acid [44].…”
Section: Polyglucuronic Acid From Bacteria Fungi and Green Algaementioning
confidence: 99%